Animal Husbandry and Nutrition - Yücel, Banu; Taşkin, Turgay (IntechOpen, 2018)
This book focuses on the animal husbandry and nutrition based on significant evaluations by the authors of the chapters. Many chapters contain general overviews on animal husbandry and nutrition from different countries. Also, the sections created shed light on futuristic overlook with improvements for animal husbandry and feeding sector. Details about rearing and feeding different animal races are also covered herein. It is hoped that this book will serve as a source of knowledge and information on animal husbandry and nutrition sector.